Cyto‐ and receptor architecture of area 32 in human and macaque brains. Issue 14 (25th July 2013) - Palomero‐Gallagher, Nicola; Zilles, Karl; Schleicher, Axel; Vogt, Brent A.
ABSTRACT Human area 32 plays crucial roles in emotion and memory consolidation. It has subgenual (s32), pregenual (p32), dorsal, and midcingulate components. We seek to determine whether macaque area 32 has subgenual and pregenual subdivisions and the extent to which they are comparable to those in humans by means of NeuN immunohistochemistry and multireceptor analysis of laminar profiles. The macaque has areas s32 and p32. In s32, layer IIIa/b neurons are larger than those of layer IIIc. This relationship is reversed in p32. Layer Va is thicker and Vb thinner in s32. Area p32 contains higher kainate, benzodiazepine (BZ), and serotonin (5‐HT)1A but lower N‐methyl‐D‐aspartate (NMDA) and α2 receptor densities. Most differences were found in layers I, II, and VI. Together, these differences support the dual nature of macaque area 32. Comparative analysis of human and macaque s32 and p32 supports equivalences in cyto‐ and receptor architecture. Although there are differences in mean areal receptor densities, there are considerable similarities at the layer level. Laminar receptor distribution patterns in each area are comparable in the two species in layers III–Va for kainate, NMDA, γ‐aminobutyric acid (GABA)B, BZ, and 5‐HT1A receptors. Multivariate statistical analysis of laminar receptor densities revealed that human s32 is more similar to macaque s32 and p32 than to human p32. Thus, macaque 32 is more complex than hitherto known. Our data suggest a homologous neural architecture in anterior cingulate s32 and p32 in human and macaque brains. J. Comp. Neurol. 521:3272–3286, 2013. © 2013 Wiley Periodicals, Inc.